Bacteriological quality of drinking water and public health inspection of refill depots: finding workable strategies to control the quality - Ishak Nurlang; Titik Nuryastuti; Mubasysyir Hasanbasri (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
Purpose: Water refill depots have increased in all areas of Indonesia. Many studies have reported concerns about the bacteriological quality of drinking water at refill depots. However, limited studies have focused on ensuring the safety and quality of drinking water in refill depots, particularly for small-scale depots. This paper examines water microbiological quality at the refill depots and their depot production inspections from the local public health authority.Method: This survey used 60% of depots (47 out of 77 depots in the district) from April 4th to May 31st, 2016, in the North Luwu District of Central Sulawesi. Water samples were taken for E. coli and coliform examination. In-depth interviews were conducted with environmental health officers at the local health authority, depot owners, and workers.Results: Almost half of the total depots (49%) failed to meet the hygiene standard. Site observation found that depots were with poor sanitation and poor water handling. Depot owners found the cost of two times a year of the bacteriological examination was too expensive, including the transportation cost of water samples to the available closest laboratory in the provincial capital.Conclusion: Depots with non-standard bacteriological quality were still high. Supervision of the depot by the district health office was very loose. Efforts to advocate the district health office to take a more assertive position are critical. Community organizations and refill water depot associations should be involved so that public health interests get attention from the local government.